Joy: A Play on the Letter "I" - Galsworthy, John, 1867-1933 (Salt Lake City, UT : Project Gutenberg, 2004)
"Joy: A Play on the Letter 'I'" by John Galsworthy is a three-act play likely written in the early 20th century. The narrative unfolds on midsummer day at Colonel Hope's house, featuring a mix of comedic and dramatic elements that explore familial relationships and the complexities of love and attraction. Central to the story are Colonel Hope, his wife Mrs. Hope, their daughter Letty and her husband Ernest Blunt, along with the intriguing character Joy, who navigates her feelings toward her mother and the adult world around her, particularly in relation to the presence of the enigmatic Maurice Lever. At the start of the play, we are introduced to Colonel Hope and Mrs. Hope as they prepare for a visit from their niece Molly and her daughter Joy. The opening scene is lively and filled with playful banter, hinting at tensions and underlying emotional dynamics, particularly between Joy and the adult figures in her life. Joy's character emerges as youthful and spirited, yet she feels overshadowed by her mother's relationship with Maurice Lever, leading to jealousy and confusion. This initial portion sets the tone for the drama to unfold, as Joy$1 (Bs complexities and the challenges faced by the adult characters foreshadow deeper conflicts related to love, loyalty, and societal expectations. (This is an automatically generated summary.)s
Release date is 2004-09-26
Produced by David Widger
Keywords: English drama